Nutritional and microbial quality of extruded fish feeds containing black soldier fly (Hermetia illucens L) larvae meal as a replacement for fish meal for tilapia (Oreochromis niloticus) and catfish (Clarius gariepinus) - Were, G.J.; Irungu, F.G.; Ngoda, P.N.; Affognon, Hippolyte D.; Ekesi, S.; Nakimbugwe, D.; Fiaboe, K.; Mutungi, C. (Informa UK Limited, 2022)
The black soldier fly (Hermetia illucens L.) is a potential substitute of fish meal in feeds. However, information on the nutrition and safety of these feeds is inadequate. This study examined the quality of fish feed pellets extruded from blends formulated with and without black soldier fly larval meal (BSFLM). A further aim was to study the influence of extrusion processing types on feed composition. Two iso-proteinous feed blends containing 28% protein were formulated with 0% BSFLM (BSFLM0) and 75% BSFLM (BSFLM75). The feed blends were then cold- or hot-extruded (CE or HE) and the products analyzed for proximate composition, amino acids, fatty acid profiles and microbial content. The BSFLM75_HE pellets contained significantly higher levels of fat (15.6%), leucine (11.5 mg/g), and oleic acid (79.1 µg/g). Hot extrusion concentrated phenylalanine and leucine, increased polyunsaturated fatty acids and saturated fatty acids and decreased total viable counts, coliforms, yeast and molds, endospores and Salmonella.